A systemic functional linguistic study of experiential meanings in tourism brochures / Tan Phim Wen - Tan, Phim Wen (2017)
The study investigates experiential meanings in tourism brochures on the topics golfing, diving and adventure from a Systemic Functional Linguistics (SFL) perspective, particularly the System of Transitivity by Halliday and Mathiessen (2014). Six tourism brochures from Malaysia and Thailand were studied which are two each on golfing, diving and adventure. The data were analysed from the System of Transitivity (Process types, Participants and Circumstantial elements). Previous studies have focused on the representation of destination images and culture in tourism brochures rather than linguistic realisations in tourism brochures (e.g. Camprubi, Guia & Comas, 2012; Hassan, 2014; Jalis, Che & Markwell, 2014). Hence, this study is significant in filling the research gap. The findings reveal that all process types were employed in all brochures. The findings show that material, relational and mental processes were the major process types in tourism brochures studied. Relational processes were mainly used in tourism brochures from Malaysia for promoting golfing while material processes were mainly used in tourism brochures from Thailand in promoting golfing. Material processes were highly used to promote diving and adventure in tourism brochures from Malaysia while relational processes were highly used to promote diving and adventure in tourism brochures from Thailand. The study concludes that two different process types, relational and material processes were highly used on the same topics of tourism brochures from Malaysia and Thailand while Circumstance of Space was highly used in all tourism brochures from Malaysia and Thailand. The study has proved that SFL is a useful analytical tool for studying authentic text and is able to bring out the implications of the language used in tourism brochures. It is hoped that the findings of the study will provide language practitioners valuable insights on how tourism brochures are written and what descriptive and persuasive features are used in them.